Algoritma K-Means Dalam Mengidentifikasikan Perkerjaan Berdasarkan Latar Belakang Pendidikan di Tingkat Rukun Warga - Sofian, Erza (I-STATEMENT, 2016)
This research is meant to identify level of unemployment based on education background that is hold each community that has graduated from university or college. The total number of graduates that graduated in each university is significant compare to available work fields, that resulted in high level of competition which made companies also set high standard in recruitment. Algorithm K-means with clustering technique can identify total population for graduates according to their root of education, age, job and available work fields. This data is produced qualitative gradually to fulfill data research needs. Therefore, it is expected that from this research can come as recommendation to each candidate or potential students in taking steps for the future and give training in accordance with their study field that graduate student or potential graduate student holds.